2014
DOI: 10.1111/acem.12333
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Following Rattlesnake Envenomation in Patients With Preenvenomation Use of Antiplatelet or Anticoagulant Medications

Abstract: Objectives: Rattlesnake envenomations commonly produce coagulopathy and thrombocytopenia, yet clinically significant bleeding is uncommon. It is unknown if patients who use antiplatelet or anticoagulant medications prior to envenomation are at increased risk for bleeding after envenomation.Methods: This was a retrospective cohort study of patients age 14 years and older who were admitted to a single academic medical center for rattlesnake envenomation. Patients who reported use of antiplatelet or anticoagulant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Only a single patient out of 450 was reported to develop a major late bleeding complication. This low incidence is consistent with two previous studies which found very low rates of late major bleeding complications [10,27].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Only a single patient out of 450 was reported to develop a major late bleeding complication. This low incidence is consistent with two previous studies which found very low rates of late major bleeding complications [10,27].…”
Section: Discussionsupporting
confidence: 93%
“…Early nuisance-type bleeding was reported in 6.3% of cases. A previous large retrospective review of patients with rattlesnake envenomation in Arizona found only 2.0% of patients to have early bleeding [10]. Considering that the NASBR population includes copperhead and cottonmouth envenomations, which are less likely to experience bleeding due to the lower incidence of venom-induced coagulopathy and thrombocytopenia, our rate of bleeding is surprisingly high.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The mechanism might have involved platelet aggregation/agglutination and the action of SVMPs on the microvessel wall [ 48 , 49 ]. Antiplatelet therapy may worsen severe bleeding [ 50 ], while administration of FFP in patients with T . s .…”
Section: Discussionmentioning
confidence: 99%